Simulations of the effect of intensive biomass burning in July 2015 on Arctic radiative budget. (December 2017) - Markowicz, K.M.; Lisok, J.; Xian, P.
Abstract: The impact of biomass burning (BB) on aerosol optical properties and radiative budget in the polar region following an intense boreal fire event in North America in July 2015 is explored in this paper. Presented data are obtained from the Navy Aerosol Analysis and Prediction System (NAAPS) reanalysis and the Fu-Liou radiative transfer model. NAAPS provides particle concentrations and aerosol optical depth (AOD) at 1° x 1° spatial and 6-hourly temporal resolution, its AOD and vertical profiles were validated with field measurements for this event. Direct aerosol radiative forcings (ARF) at the surface, the top of the atmosphere (TOA) and within the atmosphere are calculated for clear-sky and all-sky conditions, with the surface albedo and cloud properties constrained by satellite retrievals. The mean ARFs at the surface, the TOA, and within the atmosphere averaged for the north pole region (latitudes north of 75.5N) and the study period (July 5–15, 2015) are −13.1 ± 2.7, 0.3 ± 2.1, and 13.4 ± 2.7 W/m 2 for clear-sky and −7.3 ± 1.8, 5.0 ± 2.6, and 12.3 ± 1.6 W/m 2 for all-sky conditions respectively. Local ARFs can be a several times larger e.g. the clear-sky surface and TOA ARF reach over Alaska −85 and −30 W/m 2 and over Svalbard −41 and −20 W/m 2 respectively. The ARF is found negative at the surface (almost zero over high albedo region though) with the maximum forcing over the BB source region, and weaker forcing under all-sky conditions compared to the clear-sky conditions. Unlike the ARFs at the surface and within the atmosphere, which have consistent forcing signs all over the polar region, the ARF at the TOA changes signs from negative (cooling) over the source region (Alaska) to positive (heating) over bright surfaces (e.g., Greenland) because of strong surface albedo effect. NAAPS simulations also show that the transported BB particle over the Arctic are in the low-to-middle troposphere and above low-level clouds, resulting in little difference in ARFs at the TOA between clear- and all-sky conditions over the regions with high surface albedo. Over dark surfaces, the negative TOA forcing increases with AOD about 50% slower under all-sky conditions compared to clear-sky case. The boreal BB event resulted in large magnitude of ARFs and the high variabilities of the forcings over the polar region has a significant impact on the polar weather conditions and important implications for the polar climate. Highlights: Intensive boreal biomass burning event in 2015 impact on radiation budget in Arctic. Long-range transport of biomass burning aerosol in middle and lower troposphere. NAAPS model shows quite well agreement with measured AOD. Strong radiative cooling at the surface and warming at top of the atmosphere. Surface forcing efficiency exceed −100 W/m 2 /τ550 over Svalbard and Siberia.